2020
DOI: 10.4236/jbnb.2020.114014
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of <i>Citrus limonum</i> Essential Oil Based Nanoemulsion and Its Enhanced Antioxidant Activity with Stability for Transdermal Application

Abstract: Lemon oil (LO), also known as Citrus limonum is a highly volatile essential oil (EO) with potential therapeutic properties like anti-oxidative, anti-proliferative, anti-fungal and anti-cancerous. However, the efficacy of LO is limited due to its physiological factors such as high volatility, poor stability (particularly sensitive to sunlight) and quick degradability upon exposure. To overcome these challenges, we formulated lemon oil loaded nanoemulsion system (LO-NE) (oil-in-water), using aqueous titration me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…This is evident in this study, where significant instability problems such as flocculation, coalescence, and sedimentation were not detected in NE-FLO at temperatures of 4 and 25 °C. Kaur et al [ 6 ] also observed a zeta potential value lower than 30 mV, but the nanoemulsion produced had a higher stability percentage compared to the individual oil tested. Cossetin et al [ 28 ] also encountered the same situation when their nanoemulsion zeta potential value was only 11 mV, but the formulation was remarkably stable for more than three months.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is evident in this study, where significant instability problems such as flocculation, coalescence, and sedimentation were not detected in NE-FLO at temperatures of 4 and 25 °C. Kaur et al [ 6 ] also observed a zeta potential value lower than 30 mV, but the nanoemulsion produced had a higher stability percentage compared to the individual oil tested. Cossetin et al [ 28 ] also encountered the same situation when their nanoemulsion zeta potential value was only 11 mV, but the formulation was remarkably stable for more than three months.…”
Section: Resultsmentioning
confidence: 99%
“…Citrus limonum , often known as lemon oil, is a highly volatile essential oil that can be applied therapeutically due to its anti-oxidative, anti-proliferative, antibacterial, and anti-cancerous merits [ 5 , 6 ]. Lemon essential oil’s antioxidant properties benefit human skin as it undergoes environmental and chronological ageing [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation